GEnEbook: A Game Engine to Provide Electronic Gamebooks for Adventure Games - Sarinho, Victor Travassos (Anais do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames), 2021)
Gamebooks can be defined as a printed fiction that allows the reader to participate in the story by making choices. They were famous in the 80s or 90s and are reappearing today due to the combination of readers' interest with the ease of use and the presentation novelty provided by ebooks. This paper presents GEnEbook, a game engine proposal able to provide electronic gamebooks for adventure games. It uses a game data model and a multimedia game panel capable of dynamically represent gamebook adventures, together with a game builder structure able to provide valid ebook files according to security limitations defined by ebook readers. As a result, a development approach able to create interactive and gamified ebooks (the g-books) was provided, together with a reusable perspective for the fast generation of electronic gamebooks (g-books) without worrying about interpretation and execution details of compatible ebook readers.